Navigating the Intersection of Pakistan-India Relations, Climate Change, and China’s Regional Interests - Shamraiza Khan (Social Science Review Archives, 2025)
One of the most critical and pressing issues in front of the world community today is climate change. The far-reaching effects of climate change on ecosystems, economies, and food security make South Asia, home to over a billion people, an especially worrying place. In this regard, climate change poses a special challenge, especially for the two nuclear-armed nations of Pakistan and India, whose long-standing territorial disputes and resource competition have been further complicated by environmental stresses. This paper examines how the rivalry between Pakistan and India affects the management of shared environmental resources, particularly water, and how climate change exacerbates these issues. This analysis will also discuss the role of China in the region, including its strategic and environmental interests that are closely related to its growing influence in South Asia. This study highlights the need for regional cooperation in addressing the combined threats of climate change, water scarcity, and geopolitical rivalries, as well as strategies for de-escalation to ensure sustainable cooperation and regional stability.